DIRT/3D: 3D root phenotyping for field grown maize (Zea mays) - Liu, Suxing; Barrow, Carlos; Hanlon, Meredith T; Lynch, Jonathan; Bucksch, Alexander (bioRxiv, 2021)
The development of crops with deeper roots holds substantial promise to mitigate the consequences of climate change. Deeper roots are an essential factor to improve water uptake as a way to enhance crop resilience to drought, to increase nitrogen capture to reduce fertilizer inputs and to increase carbon sequestration from the atmosphere to improve soil organic fertility. A major bottleneck to achieving these improvements is high-throughput phenotyping to quantify root phenotypes of field-grown roots. We address this bottleneck with DIRT/3D, a newly developed image-based 3D root phenotyping platform, which measures 18 architecture traits from mature field-grown maize root systems. DIRT/3D reliably computed all 18 traits, including distance between whorls and the number, angles, and diameters of crown and brace roots, on a test panel of 12 contrasting maize genotypes. The computed results were validated through comparison with manual measurements. Overall, we observed a coefficient of determination of r^2>0.84 and a high broad-sense heritability of〖 H〗_mean^2> 0.6 for all important traits. The average values of the 18 traits and a newly developed descriptor to characterize a complete root architecture distinguished all genotypes. DIRT/3D is a step towards automated quantification of highly occluded maize root systems. Therefore, DIRT/3D supports breeders and root biologists in improving carbon sequestration and food security in the face of the adverse effects of climate change. Competing Interest Statement The authors have declared no competing interest.